PERMANENT PACE MAKER IMPLANTATION THROUGH AXILLARY VEIN APPROCH - Shah, Bakhawar; HUssain, Cheragh; Awan, Zahid Aslam (Journal of Ayub Medical College Abbottabad, 2017)
Background: Device implantation is an integral part of interventional cardiology particularly electrophysiology. In this study, we are going to shear our experience of device implantation technique at electrophysiology department Hayatabad Medical Complex, Peshawar. Methods: the study was conducted from June 2011 to December 2015. Axillary vein was used to implant the devices but in some cases when this rout was not convenient due to any reason then subclavian vein was entered through the Seldinger technique. Fluoroscopy time was less than 10 minutes and total procedure time was not more than 45 minutes. Electric cautery was used only in two cases. Pressure dressing was used in a few cases. Results: Total numbers of permanent pacemakers (PPM) remain 800 during the study period. There were 450 single chamber pacemakers and 350 dual chambers pacemakers. No case of any major bleeding was documented and in very few cases there was mild ooze from the procedure site after the operation which was tackled with pressure dressing. Four cases of pneumothorax were noted during the study period and in three cases chest intubation were done and one patient was kept on conservative management. Patient were followed after one moth of discharge from the hospital and then yearly. Eight cases of lead dislodgment were documented during the study period. Conclusion: Axillary vein approach for implantation of permanent pacemakers is a safe and less time-consuming technique. Keywords: Axillary vein; Permanent pacemakers (PPM); Seldinger technique; Subclavian vein